Machbarkeitsstudien für regionale Projekte - Weiß, Ute (Raumforschung und Raumordnung | Spatial Research and Planning, 2003)
What frequently makes regional projects particularly complex— compared to projects in the private sector— is the relatively large number of players involved in a project. Nonetheless, systematic studies of the chances of successful implementation remain rare. An analysis of feasibility studies of the type conventionally conducted in the private sector as an element of project management reveals precisely what project-related factors are critical for the use, design and conduct of feasibility studies. This analysis provides the basis for the author to draw up a model feasibility study for regional projects which takes full account of the specific characteristics of such projects.